Clinical researchA systematic review of Iranian medicinal plants useful in diabetes mellitus - Hasani-Ranjbar, Shirin; Larijani, Bagher; Abdollahi, Mohammad (Archives of Medical Science, 2008)
Introduction: This review focuses on the efficacy and safety of Iranian medicinal plants found effective in the management of diabetes in humans and animals. Material and methods: EMBASE, Scopus, PubMed, Web of Science, Google Scholar, and IranMedex databases were searched up to 8 October 2007. The search terms were “diabetes” and “plant”, “herb”, “traditional”, and “natural” or “herbal medicine”, limited to Iran. All of the human studies were included. Animal studies with the outcome of blood glucose or serum lipids, antioxidant effect, changes in hepatic enzymes, anti-inflammatory effect, or vascular activity in diabetes were included. Studies performed on cell lines, reviews and letters to editors were excluded. Blood glucose and serum lipids were the key outcomes. Results: Twelve human studies were reviewed for efficacy of plants. These studies showed significant decrease in blood glucose after treatment with Citrullus colocynthus L., Silybum marianum, Psyllium, Teucrium polium, and Pomegranate. Thirty-one animal studies were included showing Walnut leaf, Coriander, Pomegranate, Garlic, Satureja khuzestanica, Phlomis anisodonta, Trigonella foenum graecum, Olive (Olea europaea L.), Capsicum frutescens, Achillea santolina, Aloe vera, Salvia officinalis, Anathum graveolens, Teucrium polium, Urtica dioica, Morus nigra, Morus alba, Salvia lenifolia benth leaf, and Cynara scolymus to be significantly effective in reduction of blood glucose. Discussion: The present review indicates that some of these plants (Citrullus colocynthus, Silybum marianum, Psyllium, Teucrium polium, and Pomegranate) improve blood hyperglycemia in humans somewhat more effectively than standard chemical drugs used in diabetes. Some of these plants (Garlic, Silybum marianum, Psyllium, Teucrium polium, and Pomegranate) were found to have anti-hyperlipidaemic properties and thus can be supplemented in diabetes. Conclusions: Special attention to these effective medicinal plants will lead us to obtain novel drugs in the management of diabetes mellitus.